Ionic Liquid‐Based Redox Active Electrolytes for Supercapacitors. (24th April 2022) - Sun, Li; Zhuo, Kelei; Chen, Yujuan; Du, Quanzhou; Zhang, Suojiang; Wang, Jianji
Abstract: Supercapacitors (SCs) are fascinating energy storage devices due to their delivery of exceptional power density and long cycling stability. Unfortunately, their practical applications are still impeded by relatively inferior energy density, which is proportional to the square of the operating voltage of SCs. Ionic liquid (IL) electrolytes have a wide electrochemical stability window and thus can be used to significantly increase the energy density of SCs. The introduction of redox active species into IL‐based electrolytes effectively contributes to pseudocapacitance. Accordingly, IL‐based redox active electrolytes (IL‐REs) for SCs are springing up rapidly in recent years. This review provides an overall insight into various IL‐REs, including the ILs mixed with other redox active species, the ILs possessing redox active groups themselves, and the IL‐based redox gel polymer electrolytes for SCs. The basic understanding of IL electrolytes and IL‐REs is introduced and discussed as well as the application of the IL‐REs in SCs. Then, the energy storage mechanisms of these IL‐REs are discussed, and finally, current challenges and perspectives are highlighted for future research in this promising field. Abstract : This review gives an overall insight into the research progress of different ionic liquid (IL‐REs)‐based redox active electrolytes for supercapacitors (SCs), as well as summarizes the current challenges in this field and prospects for the development directions in the future. This review may serve as a reference to develop IL‐REs for SCs with high energy density and high‐power density.